Complex interaction of obesity, intentional weight loss and heart failure: a systematic review and meta-analysis. Issue 1 (17th September 2019) - Mahajan, Rajiv; Stokes, Michael; Elliott, Adrian; Munawar, Dian A; Khokhar, Kashif B; Thiyagarajah, Anand; Hendriks, Jeroen; Linz, Dominik; Gallagher, Celine; Kaye, David; Lau, Dennis; Sanders, Prashanthan
Abstract : Objective: The aim of the meta-analysis was to determine the association of obesity and heart failure (HF) and the cardiac impact of intentional weight loss following bariatric surgery on cardiac structure and myocardial function in obese subjects. Methods: MEDLINE, Embase and Web of Science were searched up to 3 April 2018. Studies reporting association and prognostic impact of obesity in HF and the impact of intentional weight loss following bariatric surgery on cardiac structure and myocardial function in obesity were included in the meta-analysis. Results: 4959 citations were reviewed. After exclusions, 29 studies were analysed. A 'J curve' relationship was observed between body mass index (BMI) and risk of HF with maximum risk in the morbidly obese (1.73 (95% CI 1.30 to 2.31), p<0.001, n=11). Although 'obesity paradox' was observed for all-cause mortality, the overweight group was associated with lower cardiovascular (CV) mortality (OR=0.86 (95% CI 0.79 to 0.94), n=11) with no significant differences across other BMI groups. Intentional weight loss induced by bariatric surgery in obese patients (n=9) without established HF, atrial fibrillation or known coronary artery disease, was associated with a reduction in left ventricular mass index (p<0.0001), improvement in left ventricular diastolic function (p≤0.0001) and a reduction in left atrial size (p=0.02). Conclusions: Despite the increased risk of HF with obesity, an 'obesity paradox' is observed for all-cause mortality. However, the nadir for CV mortality is observed in the overweight group. Importantly, intentional weight loss was associated with improvement in indices of cardiac structure and myocardial function in obese patients. Trial registration number: APP 74412.